Programs that Prepare Principals for Allocating Resources at the School Site: Principals and Superintendents Respond - Barbara Y. LaCost; Marilyn L: Grady (Educational Considerations, 1995)
University preparation programs...must adapt and respond to administrators' needs for a greater range of field expertise. Among these are skills and knowledge about resource allocation at decentralized sites.